Prevention of Unplanned Extubation in Pediatric Intensive Care Unit (PICU) - Kampan, Pilailak; Jampathong, Saranya; Kaewvichit, Namtip; Jaruseneenak, Pakamas (Princess of Naradhiwas University Journal, 2019)
This participatory action research in Pediatric Intensive Care Unit (PICU) aimed to: 1) study problems faced by nurses, 2) develop methods of nursing care in prevention of unplanned extubation, and 3) compare incidents when unplanned extubation occurred before and after the implementation of the developed nursing care methods. It followed four stages: 1) the planning stage, 2) the implementation stage, 3) the observation stage, and 4) the reflection and improvement stage. Data were collected by mean of group discussion, participatory observation, and review of empirical evidence. Sample was 34 nursing practitioners working in pediatric intensive care unit (PICU) ward,and 320 children being admitted at the Songklanagarind Hospital between February and July, 2018. Data were analyzed by frequency, percentage, mean, standard deviations and content analysis. The research revealed the following important findings. Firstly, most of the nursing care problems were caused by the lack of practitioners’ knowledge and know-how, attitudes and nursing care towards unplanned extubation in pediatric patients. Secondly, the developed nursing methods in treatment prevention for unplanned extubation were based on: Effective communication, Surveillance, Continuous monitoring, and Team work. Results showed that the unplanned extubation was decreased from 11.78 per one hundred days to 5.33 per one hundred days in the PICU. In conclusion, the nursing methods developed in this study were effective in preventing andreducing unplanned extubation in the PICU.